The atlas of us - Dwyer, Kristin (HarperTeen, an imprint of HarperCollinsPublishers, 2024)
Atlas James has lost her way. In a last-ditch effort to pull her life together, she's working on a community service program rehabbing trails in the Western Sierras. The only plus is that the days are so exhausting that Atlas might just be tired enough to forget that this was one of her dad's favorite places in the world. Before cancer stole him from her life, that is. Using real names is forbidden on the trail. So Atlas becomes Maps, and with her team--Books, Sugar, Junior, and King--she heads into the wilderness. As she sheds the lies she's built up as walls to protect herself, she realizes that four strangers might know her better than anyone has before. And with the end of the trail racing to meet them, Maps is left counting down the days until she returns to her old life--without her new family, and without King, who's become more than just a friend.